Targeted Therapy for Rheumatoid Arthritis in the New Era - WANG Jun; MENG Juan (Xiehe Yixue Zazhi)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease. The clinical manifestation of RA involves various organs and systems both inside and outside the joints, and often exhibits strong clinical heterogeneity with unclear pathogenesis. Ineffective drug treatment for severe arthritis can result in physical disability and severely decreased quality of life. In recent years, targeted therapy for RA has become a hot research topic and has made new breakthroughs. Targeted treatments for RA mainly include two categories: biologic and targeted synthetic disease-modifying antirheumatic drugs. This article aims to elaborate on the current research status and progress of these drugs, with the hope of providing insights for clinicians to better guide personalized treatment for RA patients.